Fast food in the city? Nomadic flying-foxes commute less and hang around for longer in urban areas. (23rd July 2021) - Meade, Jessica; Martin, John M; Welbergen, Justin A
Abstract: Urbanization creates novel ecological spaces where some species thrive. Geographical urbanization promotes human–wildlife conflict; however, we know relatively little about the drivers of biological urbanization, which poses impediments for sound wildlife management and conservation action. Flying-foxes are extremely mobile and move nomadically in response to flowering resources, but are now increasingly found in urban areas, for reasons that are poorly understood. To investigate the mechanisms behind flying-fox urbanization, we examined the movement of 99 satellite tracked grey-headed flying-foxes ( Pteropus poliocephalus ) over 1 year in urban versus non-urban environments. We found that tracked individuals preferentially visited major-urban roosts, exhibited higher fidelity to major-urban roosts, and foraged over shorter distances when roosting in major-urban areas. In contrast to other colonial species, there were no density-dependent effects of colony size on foraging distance, suggesting that at a landscape scale, flying-foxes distribute themselves across roosts in an ideal-free manner, minimizing competition over urban and non-urban foraging resources. Yet, males consistently foraged over shorter distances than females, suggesting that at a local scale foraging distances reflect competitive inequalities between individuals. Overall, our study supports the hypothesis that flying-fox urbanization is driven by increased spatiotemporal availability of food resources in urban areas; however, unlike in other species, it is likely a consequence of increased urban visitation by nomadic individuals rather than a subset of the population becoming "urban residents" per se. We discuss the implications of the movement behavior we report for the conservation and management of highly mobile species. Abstract : Urban expansion negatively impacts many species, but some, like flying-foxes, appear to thrive in the novel habitats that cities provide. Here we show that flying-foxes preferentially visited major-urban roosts; were less likely to leave major-urban roosts; and foraged closer to major-urban than non-urban roosts. Taken together, this strongly suggests that urban environments supply more spatiotemporally stable and more plentiful foraging resources than non-urban areas, providing a compelling explanation for recent flying-fox urbanization.